PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN : HANDOUT TERHADAP PRESTASI BELAJAR MAHASISWA (STUDI KASUS PADA MATA KULIAH KOMUNIKASI KEPERAWATAN DI AKADEMI KEPERAWATAN PAMENANG TAHUN 2010) - Tamsuri, Anas (Akademi Keperawatan Pamenang, 2011)
Communication in Nursing is one of subject in curriculum of Pamenang Nursing Academy which conducted to improve the studentâs knowledge and ability to perform communication between nurse and patient or her professional relatives. The subject of Communication In Nursing is a fundamentals and has main role on improving nurse performance. Due to its essence, the design of education of Communication in Nursing is essential to perform to get better result and achieve the aims of learning. The objective of this research was to identify the difference of studentâs achievement which instructed with printed material media and those instructed without printed material media. The research was qualitative method with experimental design of pre and post test design. It was conducted on Pamenang Nursing Academy on March 2010. The subjects of research were 60 students in grade I (the students of 2010). The subjects were divided into two groups. Its data were gathered through questionnaire and test. They were analyzed by using Independent-t test with a=0,05.Based on independent t-test upon both group, there were no significant difference between both groups before the treatment (instruction) with t-value = -1,821, and significance value (p)= 0,074. while after the treatment there were significant difference between both groups (t value = -5,971; p = 0,00) lower than Î± = 0,05; and according to statistic, there were significant difference between both group in the changing of achievement on pre and post test studies (t = -3,395; p= 0,001). According to the result, it is suggested to each teacher to improve their teaching material by adding printed media (dictate) and suggested to others potential researcher to perform study in such area, especially to improve the effect and power of media in improving the achievement or perform such area in wider or other field of study.